2022
DOI: 10.1007/s11356-022-24368-9
|View full text |Cite
|
Sign up to set email alerts
|

How does digital technology empower urban green development efficiency in the Beijing-Tianjin-Hebei region—mechanism analysis and spatial effects

Abstract: Under the strategy of “Digital China” and “Sustainable Development,” the synergistic development of digital economy and green economy has become a crucial topic. Based on the panel data of 13 cities in the Beijing-Tianjin-Hebei (BTH) region from 2011 to 2019, this study investigates the direct effect, intrinsic mechanism, and spatial spillover effect of digital technology development (DTD) on urban green development efficiency (GDE). The empirical results show that (1) DTD significantly improves urban GDE in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…For example, the greater the terrain undulation, the higher the technical standards required for laying internet and broadband hardware devices. In addition, mountainous terrain can also affect the transmission quality and speed of mobile network signals, thereby limiting the operational efficiency and application scenarios of DT and digital capital [89]. Air pollutants originate from the various consumption and combustion actions of human economic activities.…”
Section: Causal Recognitionalmentioning
confidence: 99%
“…For example, the greater the terrain undulation, the higher the technical standards required for laying internet and broadband hardware devices. In addition, mountainous terrain can also affect the transmission quality and speed of mobile network signals, thereby limiting the operational efficiency and application scenarios of DT and digital capital [89]. Air pollutants originate from the various consumption and combustion actions of human economic activities.…”
Section: Causal Recognitionalmentioning
confidence: 99%
“…It is found that technological innovation significantly improves UGDE [15] , and the impact of technological innovation on UGDE in eastern cities of China is greater than that in central and western cities of China, and the higher the administrative level of a city, the greater the impact of technological innovation on UGDE 26 . The development of digital technology, which belongs to one of the categories of technological innovation, significantly improves UGDE, its influence mechanism is to improve the intensity of environmental regulation and the level of technological innovation 27 . Financial agglomeration shows the periodic characteristics of diffusion and equilibrium, which have the non-equilibrium impact on UGDE 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…However, when MER is above the second threshold or VER is above the single-threshold, the development of the Internet will hinder the promotion of CEEI. Our relevant studies areGodil (2020) et al, andYang (2023) et al Godil et al (2020) pointed out that institutional quality can regulate the relationship between information and communications technologies and CO2. Yang et al (2023) pointed out in their conclusion that digital development can affect green development efficiency through environmental regulation.…”
mentioning
confidence: 99%